Peningkatan Kapasitas Pokdarwis sebagai Pengelola Rintisan Desa Wisata Timpik Kabupaten Semarang - Muarifuddin, Muarifuddin; Decky Avrilianda; Niam Wahzudik; Yahya Nur Ifriza; Dhela Septian Anggaretta (Universitas Negeri Semarang, 2025)
Timpik Village is the largest village in Susukan District, boasting beautiful views of rice fields and hills, along with fertile soil. In addition to its abundant natural resources, it also boasts a vibrant human population dedicated to advancing its village. The diverse culture and arts contribute to the development of the Tourism Awareness Group (Pokdarwis). Timpik Village, in pioneering its tourism development, focuses on the arts. The artistic culture of Timpik Village residents serves as both social capital and a tourism vehicle. The Pokdarwis serves as a leading driver for the development of the village's potential. The arts and culture it possesses serve as a source of local wisdom that must be preserved, while simultaneously upholding the mission of cultural preservation. The work program design serves as a guideline for realizing Timpik Tourism Village as a tourism village based on local cultural wisdom. Pokdarwis is able to manage existing tourism in the village, create, develop, and even create tourist destinations.